2013
DOI: 10.1589/jpts.25.737
|View full text |Cite
|
Sign up to set email alerts
|

The Intra- and Inter-rater Reliabilities of the Forward Head Posture Assessment of Normal Healthy Subjects

Abstract: [Purpose] Assessment of posture is an important goal of physical therapy interventions for preventing the progression of forward head posture (FHP). The purpose of this study was to determine the inter- and intra-rater reliabilities of the assessment of FHP. [Subjects and Methods] We recruited 45 participants (20 male subjects, 25 female subjects) from a university student population. Two physical therapists assessed FHP using images of head extension. FHP is characterized by the measurement of angles and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…FHP increases with age [20,21] and is higher in elderly than in young individuals [20][21][22][23]. FHP causes the posterior neck muscles to shorten, increases the load on the joints and ligaments, and weakens the muscles [6,24]. Eliminating FHP reduces the load on the neck.…”
Section: Discussionmentioning
confidence: 99%
“…FHP increases with age [20,21] and is higher in elderly than in young individuals [20][21][22][23]. FHP causes the posterior neck muscles to shorten, increases the load on the joints and ligaments, and weakens the muscles [6,24]. Eliminating FHP reduces the load on the neck.…”
Section: Discussionmentioning
confidence: 99%
“…Forward head posture (FHP) is one of the most common types of postural abnormality, and it is generally described as an anterior position of the head in relation to the vertical line of the body’s center of gravity 6 , 7 ) . Many researchers have reported that several factors, including headache, neck pain, and musculoskeletal disorders such as temporomandibular disorders or rounded shoulders, are related to FHP 1 , 8 ) . In addition, FHP leads to lengthening and weakness of the anterior cervical muscles as well as shortening of the posterior cervical muscles.…”
Section: Introductionmentioning
confidence: 99%
“…1 Özellikle masa başı çalışanlarda, bilgisayar önünde geçirilen süre boyunca yanlış pozisyonda oturma ve ergonomik olmayan fiziki koşullar, kişide başın anterior tilti dediğimiz üst servikal vertebraların öne, üst torakal ve alt servikal vertebraların arkaya eğim yaptığı yuvarlak omuzla birlikte olan postüre yol açar. [2][3][4] Bu yüzden boyun kas-iskelet problemleri ve servikal disfonksiyon; yuvarlak omuz postürü ve torakalkifoz ile ilişkili-dir. 3,5 Yuvarlak omuz postürü, yani omuzların öne pozisyonlanması, skapulaların protraksiyonu ile ilişkilidir ve bu durum torakal kifozda artışa neden olmaktadır.…”
Section: Bantlama Başın Anterior Tiltini Değiştirir Mi?unclassified